Me querrias tu? - Von Konigslow, Andrea Wayne; Hausner, Beatriz (Toronto : Annick Press, 1997)
Colorful illustrations and rhyming text ask questions like "Would you love a rooster that wakes people up?" or "Would you love a skunk that is stinky and smelly?"
Translation of: Would you love me?
Accelerated Reader AR
Keywords: Spanish language materials -- Fiction; Fiction